Novena, Crença e Gira Girou de Milton Nascimento e Márcio Borges: análise de suas três primeiras composições criadas em uma noite de 1964 - Wilson Lopes Cancado (2010)
Study about the first phase of the partnership between Brazilian singer-instrumentalist-composer Milton Nascimento and Brazilian lyrics writer Márcio Borges in the songs Novena, Crença e Gira Girou, composed in a night in the year 1964. It shows the influences of cinema, religious music, folklore, Brazilian popular music, instrumental music, jazz, classical music and rock. It also shows the role of the film Jules et Jim by French moviemaker François Truffaut and icon of the Nouvelle Vague movement. Based on the listening of historical recordings of Crença and Gira Girou (NASCIMENTO, 1967) and Novena (NASCIMENTO, 1993), the leadsheets of the three songs were created and were used for the analyses of form, thematic materials, harmony and text-painting. The analytical data reveal a compositional profile of an artist in formation, innovative and diverse in the Brazilian musical scene, one that still today influences generations and admirers of the Clube da Esquina (The Corners Club) in Brazil and abroad. It also includes interviews with the composers and an annotated discography.